Current status of cardiac resynchronization therapy with defibrillators and factors influencing its prognosis in Japan. Issue 3 (17th May 2013) - Shimizu, Akihiko; Mihashi, Takeshi; Furushima, Hiroshi; Sekiguchi, Yukio; Manaka, Tetsuyuki; Nishii, Nobuhiro; Ueyama, Takeshi; Yokoshiki, Hisashi; Morita, Norishige; Nitta, Takashi; Okumura, Ken
Abstract: Purpose: The purpose of this study was to clarify the prognosis of cardiac resynchronization therapy with defibrillators (CRT‐Ds) in Japan. Methods: We selected 384 patients implanted with a CRT‐D device from the observation database ( n =1482) of the Japanese Cardiac Device Therapy Registry. We investigated the CRT criteria, including the presence of New York Heart Association (NYHA) class III/IV symptoms, left ventricular ejection fraction (LVEF) ≤35%, and QRS duration ≥120 ms. The patients were divided into 2 groups: the group fulfilling all of the 3 criteria (Group A, n =229) and the group not fulfilling the criteria (Group B, n =155). We compared mortality and appropriate shock rates between the 2 groups. Results: There was no significant difference in mortality (17.9% vs. 13.5%) or appropriate shock rates (32.5% vs. 31.6%) during the observation period of 29.0±15.7 months between the 2 groups. A logistic multivariate analysis showed that appropriate shocks (hazard ratio [HR]=1.85) and class III antiarrhythmic agents (HR=2.33) were independently associated with all‐cause death, and that age ≥70 years (HR=0.55), male gender (HR=2.07), and presence of a single‐chamber device (HR=1.78) were associated with appropriate shocks. The prognosis of Group A was better than that of the COMPANION trial. Conclusions: Japanese patients with CRT‐D devices had a better prognosis than did those in the COMPANION trial, but no significant differences were observed between patients fulfilling and those not fulfilling the above mentioned criteria.